2022
DOI: 10.1101/2022.07.06.499051
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How to entrain a selected neuronal rhythm but not others: open-loop dithered brain stimulation for selective entrainment

Abstract: While brain stimulation therapies such as deep brain stimulation for Parkinson's disease can be effective, they have yet to reach their full potential across neurological disorders. Entraining neuronal rhythms using rhythmic brain stimulation has been suggested as a new therapeutic mechanism to restore neurotypical behavior in conditions such as chronic pain, depression, and Alzheimer's disease. However, theoretical and experimental evidence indicate that brain stimulation can also entrain neuronal rhythms at … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…We observed that the Poisson waveform, when compared to standard pulse stimulation at an equivalent central frequency, increases power at the central frequency while obscuring the effects of harmonics. These empirical observations support recent theoretical work showing that adding noise to the inter-pulse interval of a constant-frequency stimulation waveform ('dithering') can suppress harmonic stimulation effects [64]. There may be a quantitative tradeoff between these two properties: having low inter-pulse noise produces greater entrainment at the central frequency, but at the cost of increased harmonics; higher inter-pulse noise might lead to reduced harmonics, but also decreased entrainment at the central frequency.…”
Section: Discussionsupporting
confidence: 79%
“…We observed that the Poisson waveform, when compared to standard pulse stimulation at an equivalent central frequency, increases power at the central frequency while obscuring the effects of harmonics. These empirical observations support recent theoretical work showing that adding noise to the inter-pulse interval of a constant-frequency stimulation waveform ('dithering') can suppress harmonic stimulation effects [64]. There may be a quantitative tradeoff between these two properties: having low inter-pulse noise produces greater entrainment at the central frequency, but at the cost of increased harmonics; higher inter-pulse noise might lead to reduced harmonics, but also decreased entrainment at the central frequency.…”
Section: Discussionsupporting
confidence: 79%
“…Here we have focused predominantly on the Kuramoto model with adaptivity rules that mimic the adaptation between individual neural cells. However, as a prototypical model to study synchronization in neuroscience, the Kuramoto model has also found application on different scales including whole-brain modeling, epilepsy, and Parkinson's disease (Cumin & Unsworth, 2007;Breakspear et al, 2010;Cabral et al, 2014;Schmidt et al, 2015;Ponce-Alvarez et al, 2015;Finger et al, 2016;Asllani et al, 2018;Weerasinghe et al, 2019Weerasinghe et al, , 2021Bick et al, 2020;Duchet et al, 2022). While here each Kuramoto oscillator typically represents neural populations rather than individual cells, our results may still help understand the role of adaptivity in such networks-albeit with potentially different adaptivity rules on different timescales.…”
Section: Discussionmentioning
confidence: 80%
“…These empirical observations support recent theoretical work showing that adding noise to the inter-pulse interval of a constant-frequency stimulation waveform ("dithering") can suppress harmonic stimulation effects. 48 There may be a quantitative tradeoff between these two properties: having low inter-pulse noise produces greater entrainment at the central frequency, but at the cost of increased harmonics; higher inter-pulse noise might lead to reduced harmonics, but also decreased entrainment at the central frequency.…”
Section: Discussionmentioning
confidence: 99%